Training Workshop on developing Objective Structure Clinical Examination (OSCE) conducted at nursing campus in Nepal: Feedback of the nursing faculty participants - Piryani, Rano Mal; Piryani, Suneel (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: The aim of this study was to get feedback from the nursing faculty participants about effectiveness of training workshop on developing Objective Structure Clinical Examination and their learning experiences.Material and Methods: Seventeen faculty members participated in two and half days “Training Workshop on conducting OSCE”. There were two sessions of workshop- onsite (2 days) and online (half day). Methods used in sub-sessions of onsite session were tutorial on content, brainstorming, activity based small group work and discussion, and presentation of group work in plenary while assignment on developing OSCE for online session. The feedback of the participants was taken on semi-structured questionnaire containing seven questions; four closed and three open ended. Descriptive analysis was done in IBMS SPSS version 21.Results: Rating of the participants on training workshop was notable on rating scale 1-10 (1 poor to 10 excellent) for usefulness of training 9.65±0.70, content 9.00±1.00, relevance of training and content 9.29±0.85, facilitation 9.59±1.00 and overall rating 9.41±0.79. The level of confidence of participants after training workshop was enhanced 4.06±0.24 rated at Likert scale 1-5 for developing blueprint for assessment in related subject, test blueprint and test map and OSCE station. Useful Group work, step wise approach, interactive session, active participation and conducive environment were among the positive features of workshop.Conclusion: The feedback of the participants were constructive and remarkable. The training enhanced their level of confidence. The training was effective.